Development of an in vitro digestive model for studying the peptide profile of breast milk. (June 2015) - Dall'Asta, Chiara; Florio, Paola; Lammardo, Anna Maria; Prandi, Barbara; Mazzeo, Teresa; Budelli, Andrea; Pellegrini, Nicoletta
Abstract Human milk is a highly valuable food for newborns and infants. Its protein fraction plays an important role for the development of the newborn. In the present study, an in vitro digestive model, developed for resembling closely the digestive system of an infant, was applied to human milk in order to identify and characterize the peptide profile. The peptide profile obtained after digestion was analyzed by μLC-LTQ-Orbitrap-MS. A total of 149 peptides from β-casein, 30 peptides from α-lactalbumin, 26 peptides from αs1-casein, 24 peptides from κ-casein, 28 peptides from osteopontin, and 29 from lactoferrin was recovered. The identified peptide profile of partially hydrolyzed proteins, such as caseins, α-lactalbumin, and osteopontin, was different from that previously reported demonstrating a different performance of the developed neonatal digestive system with respect to other previously applied. These results would be useful as a starting point to investigate the physiological function of breast milk peptides.